Effect of Variation of the Slope of Parshall Flume Floor on its Discharge Rating - Singh, A P; Rajput, TBS (Journal of Agricultural Engineering, 2003)
Dimensions of all design parameters of ten Parshall flumes of 3 in. (76.2 mm) size, in use at four distant locations were recorded and their manufacturing variations were determined. Variations up to 30 per cent were observed in case of bottom slopes whereas all other parameters were found to be manufactured within an accuracy of ± 5 per cent. Head discharge relationships were developed for flumes having different upward bottom slopes (3degree 16' to 6degree 32') and downward bottom slopes ( 9degree 1' to 25degree 12') of diverging and throat sections, respectively, of a 76.2 mm size Parshall flume. Variations between the actual discharge passing through the flumes of varying bottom slopes (other than the standards), and the observed discharge (calculated on the basis of observed head of water), were noted. Based on regression analysis, a correction factor (Y) was proposed for estimating actual discharges from the flumes having bottom slopes from 9degree to 25degree ,Y = 0.8323 + 0.5064 X1 -0.3601 X2 (where X1 and X2 are down- slope and upslope of the flume bottom, respectively.